2015
DOI: 10.17221/8382-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of post-weaning diarrhoea in piglets by zinc oxide and sodium humate

Abstract: ABSTRACT:The high prophylactic doses of ZnO commonly used to control post-weaning diarrhoea (PWD) in piglets have become an environmental problem. The possibility of partial replacement of ZnO by sodium humate (HNa) in PWD treatment was investigated in this study. Weaned piglets (32) were challenged with two enterotoxigenic E. coli strains (ETEC/O149/F4/LT and ETEC/O147/F18/LT) and allocated into four treatments maintained for three weeks: C (no supplementation); ZnO2.5 (2.5 g ZnO/kg diet); HNa + ZnO1.0; HNa +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
2
21
0
2
Order By: Relevance
“…The high FCR in the ETEC-infected control group reflected the poor health status and growth depression of piglets in comparison with the lower FCR in groups supplemented with ZnO and HNa + ZnO. These results are in accordance with those in our previous experiments in which we confirmed the possibility of reducing the high pharmacological dose of ZnO in PWD treatment through partial replacement with HNa (Trckova et al 2015). To the best of our knowledge, there are no data on the use of HS in the prophylaxis of ETEC-induced diarrhoea in piglets.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The high FCR in the ETEC-infected control group reflected the poor health status and growth depression of piglets in comparison with the lower FCR in groups supplemented with ZnO and HNa + ZnO. These results are in accordance with those in our previous experiments in which we confirmed the possibility of reducing the high pharmacological dose of ZnO in PWD treatment through partial replacement with HNa (Trckova et al 2015). To the best of our knowledge, there are no data on the use of HS in the prophylaxis of ETEC-induced diarrhoea in piglets.…”
Section: Discussionsupporting
confidence: 91%
“…HS in pig diet was also shown to improve growth performance, meat quality, increase the nutrient digestibility and reduce ammonia emission from manure (Ji et al 2006;Wang et al 2008;Pisarikova et al 2010). Our previous studies showed that sodium humate (HNa) was insufficient for the treatment of diarrhoea in piglets challenged by pathogenic strains of Escherichia coli and that in the case of severe diarrhoeal infections supplementation of HNa to piglets can be effective only in combination with a specific dose of ZnO (1700 mg/kg; Trckova et al 2015). However, to what extent the prophylactic effect of HNa and ZnO was due to the maintenance of intestinal health and stabilisation of microbiota after treatment was not determined.…”
mentioning
confidence: 99%
“…There are ongoing efforts aimed at finding effective alternatives, that could protect piglets from post-weaning diarrhoea and growth depression after weaning. In our previous studies (Trckova et al 2015;Kaevska et al 2016) we verified the possibility of the substitution of a pharmacological dose of ZnO (2.5 g/kg diet) by humic substances (HS). HS are natural bioactive agents primarily decomposed from organic matter by bacteria in the soil.…”
mentioning
confidence: 65%
“…EMEA (1999) has recommended humic acid (HA) and its sodium salt for the treatment of diarrhoea, dyspepsia and acute intoxications in animals. However, our previous results showed that in cases of severe post-weaning diarrhoeal infections caused by enterotoxigenic Escherichia coli strains (ETEC), supplementation of HS to piglets can be adequately effective only in combination with a specific dose of ZnO (1.7 g/kg; Trckova et al 2015). Moreover, there is still a lack of data about other potential effects of this partial substitution of ZnO by HS on the young and vulnerable organism of weaning piglets.…”
mentioning
confidence: 99%
“…This suggests that ZnO protects the small intestine from weaning-associated damage, which could be the reason behind the decreased diarrhoea incidence. Supplementation of piglet diets with a high ZnO dose (2.5 g/kg diet) or a lower ZnO dose (1.7 g/kg diet) supplemented with sodium humate (20.0 g/kg diet) was in both cases shown to be effective in the prophylaxis of post-weaning diarrhoea (Trckova et al 2015). Supplementing a pea protein-based diet with 2880 mg of Zn/kg not only reduced the incidence of diarrhoea, but also expedited the recovery of piglets in this treatment group to within four days of E. coli administration; by contrast, piglets fed a diet without ZnO continued to shed E. coli K88 and had severe diarrhoea (Owusu-Asiedu et al 2003).…”
Section: Discussionmentioning
confidence: 99%